2022
DOI: 10.3390/su14073831
|View full text |Cite
|
Sign up to set email alerts
|

Marble Dust Effect on the Air Quality: An Environmental Assessment Approach

Abstract: All over the world, increasing anthropogenic activities, industrialization, and urbanization have intensified the emissions of various pollutants that cause air pollution. Marble quarries in Pakistan are abundant and there is a plethora of small- and large-scale industries, including mining and marble-based industries. The air pollution caused by the dust generated in the process of crushing and extracting marble can cause serious problems to the general physiological functions of plants and it affects human l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Marble processing at this site not only contaminates the outdoor and indoor air but also causes hearing loss and hearing disturbances due to noise pollution in the exposed population (Kaleem, 2018). Studies have suggested that particulate matter and noise emitted from marble factories are accountable for various health effects in workers and exposed population (Madhoun et al, 2013;Iqbal et al, 2022). The maximum concentration had reached approximately 400 µg/m 3 before lockdown whereas that had decreased to below 100 µg/m 3 during lockdown.…”
Section: Monitoring Of Particulate Matter (Pm25)mentioning
confidence: 99%
“…Marble processing at this site not only contaminates the outdoor and indoor air but also causes hearing loss and hearing disturbances due to noise pollution in the exposed population (Kaleem, 2018). Studies have suggested that particulate matter and noise emitted from marble factories are accountable for various health effects in workers and exposed population (Madhoun et al, 2013;Iqbal et al, 2022). The maximum concentration had reached approximately 400 µg/m 3 before lockdown whereas that had decreased to below 100 µg/m 3 during lockdown.…”
Section: Monitoring Of Particulate Matter (Pm25)mentioning
confidence: 99%
“…Dust generated during the processing, cutting, and polishing of marble is collected and discharged near the manufacturing plants. The high alkalinity of these deposits reduces soil fertility and increases the risk of water contamination (3,4). In addition, the fine marble particles suspended in the air can cause respiratory, visual, and skin disorders (5), (6).…”
Section: Introductionmentioning
confidence: 99%
“…Turkey is among the wealthiest countries in the world in terms of marble, with a total of 5.2 billion m 3 (13.9 billion tons) of marble reserves, which has approximately 40% of the world's resources [10]. In Turkey, 40-60% of the 7 million tons of marble produced annually, which can be expressed as a million tons, is dumped on the roadsides or around the production facilities [11]. Concrete is exposed to many physical and chemical effects depending on the time during its service life, and therefore its strength and durability properties are significantly reduced.…”
Section: Introductionmentioning
confidence: 99%